Reaction kinetics of lactic acid fermentation from bitter cassava (Manihot glaziovii) starch by Lactobacillus casei - Setiyo Gunawan; Nurul Rahmawati; Rona Bening Larasati; Ira Dwitasari; Hakun Wirawasista Aparamarta; Tri Widjaja (Universitas Gadjah Mada, 2021)
One of the utilizations of bitter cassava is modified cassava flour (Mocaf) production using the fermentation process by Lactobacillus casei. The Mocaf has potential as the future of food security products. It has a characteristic property similar to wheat flour. Lactic acid was also produced as a by‐product during fermentation. After 40 h of fermentation, the proximate composition content of Mocaf was lactic acid content of 0.000928 g/L, hydrogen cyanide levels of 0.02 ppm, starch content of 59.13%, amylose content of 12.98% and amylopectin content of 46.15%. In the scaling‐up process from a laboratory scale to a pilot and industrial scale, modeling is needed. There are five equation models used to describe the kinetic reactions of lactic acid from bitter cassava starch: Monod, Moser, Powell, Blackman, and Product Inhibitor. Each parameter was being searched by a fitting curve using sigmaplot 12.0. The best result in terms of the highest R2 (0.65913) was obtained in the Powell equation with the value of µmax of 1.668/h, Ks of 123.4 g/L, and maintenance rate (m) of 4.672. The kinetic data obtained can be used to design biochemical reactors for industrial scale Mocaf flour production.